A Multi-LED Collaborated Signal Design for MISO VLC Systems Based on Amplitude-Phase Superposition - Wen-Ya Wang; Yi-Jun Zhu (IEEE Photonics Journal)
In this paper, a multiple light-emitting diode (LED) collaborated signal design based on amplitude-phase superposition (MLC-APS) for multi-input single-output visible light communication (VLC) systems is proposed. By using the additive unique factorization technique, all the LED chips can be viewed as transmitting in parallel to increase the rate of VLC systems. In the MLC-APS system, each LED adopts on–off-keying (OOK) modulation, and therefore, the influences of peak-to-average power ratio and clipping are reduced significantly. Simulation results show its significant error performance gains over the direct-current-biased optical orthogonal frequency division multiplexing (OFDM) system.